Atherosclerosis and renal disease involvement in patients with systemic lupus erythematosus: a cross-sectional cohort study. (16th July 2018) - Hermansen, Marie-Louise; Sandholt, Benjamin; Fuchs, Andreas; Sillesen, Henrik; Køber, Lars; Kofoed, Klaus Fuglsang; Faurschou, Mikkel; Jacobsen, Søren
Abstract: Objective: To investigate the association between LN, renal function and atherosclerosis measured by coronary artery calcium (CAC) and carotid plaque in a cross-sectional study of patients with SLE. Methods: Presence of CAC and carotid plaque was measured in 147 SLE patients with and without LN. The patients were divided into four groups according to LN and renal function [by first quartile of estimated glomerular filtration rate (eGFR): 70 ml/min/1.73 m 2 ]. Impaired renal function was defined by an eGFR <70 ml/min/1.73 m 2 . We used multivariate logistic regression models to explore the association between LN, renal function, CAC and carotid plaque. Results: Of the 147 SLE patients, 74 had LN. Median age of the study cohort was 46 years, 89% were women and median eGFR was 89 ml/min/1.73 m 2 . CAC score >0 was present in 57 (39%) and carotid plaque in 29 (20%) of the SLE patients. The presence of CAC and/or carotid plaque was highest in SLE patients with impaired renal function. Regression analyses showed that compared with SLE patients without LN and eGFR ⩾70 ml/min/1.73 m 2 (reference group), only the combination of LN and impaired renal function was associated with the presence of CAC (odds ratio: 6.82, 95% CI: 1.59, 29; P = 0.01) and carotid plaque (odds ratio: 5.60, 95% CI: 1.19, 26; P = 0.03). Conclusion: Our findings indicate that LN in combination with impaired renal function defined by an eGFR <70 ml/min/1.73 m 2 is strongly associated with the presence of atherosclerosis in SLE.